Implementasi Keberadaan Bandara Kuala Namu dalam Pemetaan Sosial Ekonomi UMKM Sekitarnya - Syafrida Damanik; M Umar Maya Putra (Universitas Medan Area, 2020)
This research is a technical study of the existence of Kuala Namu Airport in Deli Serdang Regency which is surrounded by Micro, Small and Medium Enterprises (MSMEs). MSMEs need to understand socio-economic mapping as a driving force for the development of Deli Serdang Regency and can play an important role in the existence of Kuala Namu Airport. This concept can be used as an indicator to provide useful solutions in increasing outputs and outcomes. The method used is a qualitative method which is transferred into a quantitative method to map the general potential of them around Kuala Namu Airport as many as 34 MSMEs. From the research results, the main problems of marketing in the Covid 19 pandemic era need to be resolved comprehensively and need assistance from the Government to conduct entrepreneurship training and business promotion based on go international